Laser Interstitial Thermal Therapy for Radionecrosis - Terrapon, Alexis Paul Romain; Krüger, Marie; Hundsberger, Thomas; Neidert, Marian Christoph; Bozinov, Oliver (Neurosurgery clinics of North America, 2023)
Radiotherapy is widely used for brain tumors but can cause radiation necrosis (RN). Laser interstitial thermal therapy (LITT) is a relatively new therapeutic modality for RN and its impact on patient outcome is still not well understood. Based on a systematic literature search (n=33), the authors discuss the available evidence. Most studies found a positive safety/efficacy profile, as LITT may help to lengthen survival, prevent progression, taper steroids, and improve neurological symptoms while remaining safe. Prospective studies on this subject are needed and may result in LITT becoming an essential therapeutic option for the treatment of RN.